2002
DOI: 10.1207/s15327590ijhc143&4_06
|View full text |Cite
|
Sign up to set email alerts
|

That's Entertainment! Designing Streaming, Multimedia Web Experiences

Abstract: This article investigates the use of streaming multimedia narratives in Web entertainment. Based on experience gained during the user-centered design of a Web site for art and culture, evidence is provided that users want and like "less clicking, more watching" Web experiences where the point of view of experts, artists, or celebrities is presented in a narrative form. A study was conducted where users evaluated 2 prototypes of cultural tours that stream continuously for several minutes unless the user chooses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…People are entertained when an experience interests them and gives them some amount of pleasure or release (Karat et al, 2002). A website may score high on entertainment by being funny, using interesting themes, nice graphics, or appealing designs (Chakraborty et al, 2003;Chen et al, 2002).…”
Section: Online Entertainmentmentioning
confidence: 99%
“…People are entertained when an experience interests them and gives them some amount of pleasure or release (Karat et al, 2002). A website may score high on entertainment by being funny, using interesting themes, nice graphics, or appealing designs (Chakraborty et al, 2003;Chen et al, 2002).…”
Section: Online Entertainmentmentioning
confidence: 99%
“…Streaming video requires less clicking, less engagement, and more watching. Karat et al (2002) examined user response to streaming video/audio in company-sponsored websites. The material contained a short documentary within a browser, and the experimenters recorded all mouse movement on the screen as a measure of subjects' interactivity.…”
Section: Journal Of Computer-mediated Communication 14 (2009) 581-601mentioning
confidence: 99%
“…The relationship between entertainment and engagement has long been recognised as the key in the adoption of social robots (e.g. Karat et al, 2002;Coulter et al, 2012;Schodde et al, 2017;Liu et al, 2019). Further, studies in advertising have indicated that positive mood does not always generate positive evaluations (Yan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%